Innovación y desarrollo en el tratamiento y disposición de cortes de perforación (2017)
This monograph presents the current state of applied technologies for the treatment and disposal of drilling cuts, the level of innovation is analyzed from the new methodologies, such as the "All Natural" treatment technology, the combination of a cleansing agent synthesized with an ultrasonic source and the enhanced CRI reinjection; highlighting in this way its characteristics, treatment efficiency, application times, advantages and limitations.